The effect of different hormone treatments upon the breeding and lambing performance of ewes. - Bell, T.D.; Smith, W.H.; Johnson, M. (Kansas Agricultural Experiment Station, 2012)
Approximately 350 ewes, largely of western origin, were included in three outlying experimental flocks. Approximately one-third of each flock received a series of five injections of progesterone (30 mg. each) at three-day intervals and an injection of 500 IU of P.M.S. material, either "Gonaden" or "Gonadogen," three days following the last injection of progesterone. One group of ewes in the larger flock received only four injections of progesterone before receiving their P.M.S. injection.
Keywords: Sheep; Hormone; Breeding; Lambing; Performance